Alternative Criminal Punishments for the Settlement of Misdemeanor in a Social Justice Perspective - Zulyadi, Rizkan; Hossain, Mohammad Belayet (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
The national law has a clear vision to realize a just and democratic rule of law. Criminal legal system serves to protect the interests of the society and the nation. Criminal law enforcement nowadays is no longer directed at enforcing crimes, but also to cope with humanitarian interest in criminal actions, especially when it has to defend against misdemeanor. This paper aims to analyze the current dynamics in how Indonesian criminal law contextualize its existence in facing misdemeanor. By using juridical and normative approach with descriptive analytical technique, the results showed inadaptability of criminal law with misdemeanor cases. The results highlight that as a complex part of socio-economic and legal problem, misdemeanor is dynamically challenging legal system and criminalization. This study demonstrated the need for alternative penalties for minor crimes as an integral part of reforming the Indonesian Criminal Code. More specifically, this study shows several requirements that need to be met in the legalization of alternative criminal penalties for minor crimes. In addition, alternative punishments can provide benefits to the community, such as involving criminals in community service and unpaid work. The recommendations are pointed out regarding the application of alternative criminal penalties for minor crimes.